1999
DOI: 10.1128/mcb.19.4.2556
|View full text |Cite
|
Sign up to set email alerts
|

Parental Allele-Specific Chromatin Configuration in a Boundary–Imprinting-Control Element Upstream of the Mouse H19 Gene

Abstract: The mouse H19 gene is expressed from the maternal chromosome exclusively. A 2-kb region at 2 to 4 kb upstream of H19 is paternally methylated throughout development, and these sequences are necessary for the imprinted expression of both H19 and the 5 -neighboring Igf2 gene. In particular, on the maternal chromosome this element appears to insulate the Igf2 gene from enhancers located downstream of H19. We analyzed the chromatin organization of this element by assaying its sensitivity to nucleases in nuclei. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 62 publications
7
50
0
Order By: Relevance
“…ES cells carry the maternal-specific DNA methylation imprint on the Air promoter (Stoger et al 1993), which indicates that the presence of the DHS on the paternal allele likely correlates with the absence of DNA methylation. Regulation of constitutive DHS by DNA methylation may be a common feature of imprinted genes and ICEs, as similar results were found at the H 1 9 D M D a n d t h e P r a d e r -W i l l i / Angelman ICE (Khosla et al 1999;Perk et al 2002) and the mouse U2af1-rs1 and the Nespas/Gnasxl promoters Coombes et al 2003). CpG island promoters have been suggested to create open chromatin by default and to constitutively bind ubiquitous transcription factors in the absence of gene expression (Antequera 2003).…”
Section: Dhs Mapping To Interspersed Repeatssupporting
confidence: 66%
“…ES cells carry the maternal-specific DNA methylation imprint on the Air promoter (Stoger et al 1993), which indicates that the presence of the DHS on the paternal allele likely correlates with the absence of DNA methylation. Regulation of constitutive DHS by DNA methylation may be a common feature of imprinted genes and ICEs, as similar results were found at the H 1 9 D M D a n d t h e P r a d e r -W i l l i / Angelman ICE (Khosla et al 1999;Perk et al 2002) and the mouse U2af1-rs1 and the Nespas/Gnasxl promoters Coombes et al 2003). CpG island promoters have been suggested to create open chromatin by default and to constitutively bind ubiquitous transcription factors in the absence of gene expression (Antequera 2003).…”
Section: Dhs Mapping To Interspersed Repeatssupporting
confidence: 66%
“…HSS in EG-1 embryonic germ cell line (derived from 8,5 dpc mouse embryo PGCs) may be due to the fact that erasure of imprinting of the H19 gene has not yet happened at this stage of development (Hajkova et al, 2002;Li et al, 2004;Trasler, 2006). Consistently, other authors have detected HSS in maternal alleles of somatic cells from several tissues with and without gene expression (Hark and Tilghman, 1998;Khosla et al, 1999), suggesting that the presence of HSS might be constitutively associated with H19 maternal alleles. In summary, our results suggest that the establishment of imprinting in the male germ cell line is gene specific and that this process does not occur during a single stage of development.…”
Section: B C D Esupporting
confidence: 67%
“…Intriguingly, a detailed examination revealed that some of the CTCF target sites map to linker regions which are flanked by positioned nucleosomes on the maternally inherited allele (12,13). This interpretation has been contended by others who argue that the multiple nuclease hypersensitive sites, some of which depend on CTCF, reflect a nucleosome-free region within the H19 ICR (9,15). Given the functional importance of the H19 ICR, we decided to examine the issue of nucleosome positioning more closely by insertional mutagenesis of episomal H19 ICR, followed by transfection and chromatin conformation analyses in stably transfected cells.…”
mentioning
confidence: 99%